Obtenção de fibras de poli (ácido lático): cerâmica para aplicação em sistemas de liberação prolongada da cloxacilina - Sá, Mayara Coelho (Universidade Federal de São Carlos, 2020)
The excessive consumption of these drugs can cause the development of superbugs capable of resisting treatments in humans, in addition to environmental consequences. Among the alternatives used, fibers obtained by electrospinning stand out as a simple and low cost strategy, increasing the bioavailability of an active principle at an infected site, for example, reaching therapeutic levels with a single dose. Thus, the objective of this work was to obtain fiber polylactic acid: starch: clay for controlled / prolonged drug release. The fibers were produced using electrospinning technique in which four different systems were developed: polylactic acid; polylactic acid and starch; polylactic, starch and laponite; polylactic acid, starch and montmorillonite. However, for each system developed, benzathine and sodium cloxacillin were tested. Bactericidal tests were carried out with all samples against the bacteria S. aureus and E. coli. In addition, mechanical analysis of the developed systems was carried out. The release tests were carried out in buffered pH 7 solutions and the drugs were quantified with the aid of an ultraviolet-visible spectrophotometer. The results indicated that the fibers of the polylactic acid starch and montmorillonite system showed higher values of tension and deformation, approximately 4 times, when compared to the polylactic acid fibers. In the release tests, controlled/prolonged release profiles were observed, by adding clays, laponite and montmorillonite, which were adjusted by the Korsmeyer-Peppas model. In the other systems, burst release profiles were observed. Microbiological tests for these systems, using benzathine and sodium cloxacillin, have shown bactericidal activity against the bacterium S. aureus. Therefore, systems that contain clays are promising for application involving the release of cloxacillins, especially those that require dosage, whose concentration remains for a long time in the therapeutic range of this medication
Obtaining poly (lactic acid) fibers: ceramic for cloxacillin prolonged release systems
Keywords: Eletrofiação; Liberação de fármaco; Nanofibras; Amido; Poli (ácido láctico); Electrospinning; Drug delivery; Nanofibers; Starch; Poly (acid lactic); CIENCIAS EXATAS E DA TERRA::QUIMICA